IL-12p40/IL-23p40 Blockade With Ustekinumab Decreases the Synovial Inflammatory Infiltrate Through Modulation of Multiple Signaling Pathways Including MAPK-ERK and Wnt - Fiechter, Renée H.; de Jong, Henriëtte M.; van Mens, Leonieke J. J.; Fluri, Inka A.; Tas, Sander W.; Baeten, Dominique L. P.; Yeremenko, Nataliya G.; van de Sande, Marleen G. H. (Frontiers in Immunology, 2021)
Psoriatic arthritis (PsA) is a chronic inflammatory joint disease within the spondyloarthritis spectrum. IL-12p40/IL-23p40 blockade reduces PsA disease activity, but its impact on synovial inflammation remains unclear. Objectives To investigate the cellular and molecular pathways affected by IL-12p40/IL-23p40 blockade with ustekinumab in the synovium of PsA patients. Methods Eleven PsA patients with at least one inflamed knee or ankle joint were included in a 24-week single-center open-label study and received ustekinumab 45 mg/sc according to standard care at week 0, 4 and 16. Besides clinical outcomes, synovial tissue(ST) samples were obtained by needle arthroscopy from an inflamed knee or ankle joint at baseline, week 12 and 24 and analyzed by immunohistochemistry, RNA-sequencing and real-time quantitative polymerase chain reaction(qPCR). Results We obtained paired baseline and week 12, and paired baseline, week 12 and 24 ST samples from nine and six patients, respectively. Eight patients completed 24 weeks of clinical follow-up. At 12 weeks 6/11 patients met ACR20, 2/11 met ACR50 and 1/11 met ACR70 improvement criteria, at 24 weeks this was 3/8, 2/8 and 1/8 patients, respectively. Clinical and serological markers improved significantly. No serious adverse events occurred. We observed numerical decreases of all infiltrating cell subtypes at week 12, reaching statistical significance for CD68+ sublining macrophages. For some cell types this was even more pronounced at week 24, but clearly synovial inflammation was incompletely resolved. IL-17A and F, TNF, IL-6, IL-8, and IL-12p40 were not significantly downregulated in qPCR analysis of W12 total biopsies, only MMP3 and IL-23p19 were significantly decreased. RNA-seq analysis revealed 178 significantly differentially expressed genes between baseline and 12 weeks(FDR 0.1). Gene Ontology and KEGG terms enrichment analyses identified overrepresentation of biological processes as response to reactive oxygen species, chemotaxis, migration and angiogenesis as well as MAPK-ERK and PI3K-Akt signaling among the downregulated genes and of Wnt signaling among the upregulated genes. Furthermore, ACR20 responders and non-responders differed strikingly in gene expression profiles in a post-hoc exploratory analysis. Conclusions Ustekinumab suppresses PsA synovial inflammation through modulation of multiple signal transduction pathways, including MAPK-ERK, Wnt and potentially PI3K-Akt signaling, rather than by directly impacting the IL-17 pathway.